Produção e composição do óleo essencial de manjericão (Ocimum basilicum L.) sob doses de cama de frango - Morais, Tatiane Pereira dos Santos (2006)
Essential oil of basil (Ocimum basilicum L.) with high concentration of linalool is valued in the international market and widely used in the industries of condiments and cosmetics. It has few information regarding the basil culture (Ocimum basilicum L.), therefore this research has the objective to evaluate the yield and the quality of essential oil of genotypes of basil in function of levels of organic fertilization in the conditions of winter with irrigation. The experiment was lead in the Farm Experiment of the Glory, pertaining to the Federal University of Uberlândia, in the period of 21 of May the 7 of October of 2005. Five levels of fertilization, being 2, 4, 6, 8 and 10 had been used kg of organic fertilizer (chicken manure)/m2. The used experimental delineation design was completely randomized and divided in groups with four replications. Two genotypes had been sown: Basil PI 197442 S3 Bulk 13 (G1) and Basil NSL 6421 S3 Bulk 14 (G2). Hydrodistillation with Clevenger Modified for extration of the essential oil had been made. The analyzed variable had been: height of the plant; length and width of leaf; relation length/width (C/L); essential oil yield , yield of linalool in the essential oil, with cool and dry mass of leves and flowers. The doses of chicken manure had significantly influenced the cool yield of linalool of distilled essential oil with mass and dry of both the genotypes, being the other variable had not presented significant differences.